The quest for artificial intelligence : a history of ideas and achievements - Nilsson, Nils J. (Cambridge : Cambridge University Press, 2010)
Artificial intelligence (AI) is a field within computer science that is attempting to build enhanced intelligence into computer systems. This book traces the history of the subject, from the early dreams of eighteenth-century (and earlier) pioneers to the more successful work of today$1 (Bs AI engineers. AI is becoming more and more a part of everyone$1 (Bs life. The technology is already embedded in face-recognizing cameras, speech-recognition software, Internet search engines, and health-care robots, among other applications. The book$1 (Bs many diagrams and easy-to-understand descriptions of AI programs will help the casual reader gain an understanding of how these and other AI systems actually work. Its thorough (but unobtrusive) end-of-chapter notes containing citations to important source materials will be of great use to AI scholars and researchers. This book promises to be the definitive history of a field that has captivated the imaginations of scientists, philosophers, and writers for centuries. The definitive history of artificial intelligence (AI), from the dreams of early pioneers to the achievements of modern research. The book includes many diagrams and easy-to-understand descriptions of AI programs that will help the casual reader gain an understanding of how these and other AI systems actually work.s
Part I. Beginnings: 1. Dreams and dreamers; 2. Clues; Part II. Early Explorations: 1950s and 1960s: 3. Gatherings; 4. Pattern recognition; 5. Early heuristic programs; 6. Semantic representations; 7. Natural language processing; 8. 1960s infrastructure; Part III. Efflorescence: Mid-1960s to Mid-1970s: 9. Computer vision; 10. 'Hand-Eye' research; 11. Knowledge representation and reasoning; 12. Mobile robots; 13. Progress in natural language processing; 14. Game playing; 15. The dendral project; 16. Conferences, books, and funding; Part IV. Applications and Specializations: 1970s to Early 1980s: 17. Speech recognition and understanding systems; 18. Consulting systems; 19. Understanding queries and signals; 20. Progress in computer vision; 21. Boomtimes; Part V. 'New Generation' Projects: 22. The Japanese create a stir; 23. Darpa's strategic computing program; Part VI. Entr'acte: 24. Speed bumps; 25. Controversies and alternative paradigms; Part VII. The Growing Armamentarium: From the 1980s Onward: 26. Reasoning and representation; 27. Other approaches to reasoning and representation; 28. Bayesian networks; 29. Machine learning; 30. Natural languages and natural scenes; 31. Intelligent system architectures; Part VIII. Modern AI: Today and Tomorrow: 32. Extraordinary achievements; 33. Ubiquitous artificial intelligence; 34. Smart tools; 35. The quest continues.
Includes bibliographical references and index.
Keywords: ARTIFICIAL INTELLIGENCE -- HISTORY